2003
DOI: 10.1089/107999003322485099
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-Inducible Chemokines Enhance Adaptive Immunity and Colitis

Abstract: T helper type 1 (Th1) cells secreting interferon-gamma (IFN-gamma) have been closely associated with Crohn's disease (CD). Monokine-induced by IFN-gamma (MIG), IFN-gamma-inducible T cell alpha chemoattractant (I-TAC), and IFN-gamma-inducible protein-10 (IP-10), are chemokines that bind CXCR3 and mediate the chemotaxis of leukocytes. IP-10, MIG, and CXCR3 have been shown to be expressed at sites of CD. The current study stems from our recent findings that IP-10, MIG, and I-TAC significantly contribute to the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
64
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 64 publications
2
64
0
Order By: Relevance
“…Both of these glutamate-leucine-arginine-negative CXC chemokines have the capacity to attract and retain activated T cells (58,59), and they both have been shown to have significant angiostatic activity that contributes to the inhibition of human NSCLC tumorigenesis and spontaneous metastases (60,61). Collectively, these findings illustrate the importance and potential capacity of fibroblasts in the tumor microenvironment to attract, retain, and modulate the activation of tumor-associated lymphocytes and to directly and indirectly alter the local progression and metastasis of human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these glutamate-leucine-arginine-negative CXC chemokines have the capacity to attract and retain activated T cells (58,59), and they both have been shown to have significant angiostatic activity that contributes to the inhibition of human NSCLC tumorigenesis and spontaneous metastases (60,61). Collectively, these findings illustrate the importance and potential capacity of fibroblasts in the tumor microenvironment to attract, retain, and modulate the activation of tumor-associated lymphocytes and to directly and indirectly alter the local progression and metastasis of human tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that its expression can be specifically induced as the disease progresses. Previous studies have shown that CRC cells can produce CXCL10 (31) and that CXCL10 functions as a major chemoattractant for activated T cells and natural killer cells (33,34). Various studies have strongly suggested a role for CXCL10 in the regulation of angiogenesis activity in tumorigenesis (34), as well as in direct metastasis-promoting activities in CRC cells, and its influence in the tumor microenvironment (35).…”
Section: Discussionmentioning
confidence: 99%
“…CXC chemokines are important for enhancing immunity, regulating angiogenesis, and mediating tumor cell metastases (7). CXCL10, human interferon-inducible protein 10 (IP-10), acts through putative receptor CXC receptor 3 (CXCR3), and functions as a major chemoattractant for activated T cells and natural killer cells (8)(9)(10). Recently, numerous studies into the role of CXCL10 in malignancy have shown two tumor inhibiting properties that influence cells in the tumor microenvironment (11).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, numerous studies into the role of CXCL10 in malignancy have shown two tumor inhibiting properties that influence cells in the tumor microenvironment (11). One property is the recruitment into tumor sites of CXCR3-expressing mononuclear cells with antitumor activity and the other is antagonizing the effects of powerful angiogenic factors (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%